Factors related to missed opportunities for immunization at urban and suburban primary health centers in Medan - Oke Rina Ramayani; Ridwan M. Daulay; Sri Sofyani; Iskandar Z. Lubis (Indonesian Pediatric Society, 2007)
Background Missed opportunites for immunization is one of theimportant causes of low immunization coverage that should beprevented.Objective To investigate missed opportunities for immunizationand related factors at urban and suburban primary health centersin Medan.Methods A cross sectional study was conducted between January-March 2004. Primary health centers in Medan were divided intourban (20 primary health centers) and suburban (19 primaryhealth centers) groups. The sample size was 109 children whovisited primary health centers for immunization. Study was doneby a questionnaire taken after infants received immunization (exitinterview).Results The proportion of missed opportunities in urban andsuburban area was 22.3% (95% CI 16.9%;27.7%) and 29.9% (95%CI 24.0%;35.2%) (P=0.191), respectively. Factors such as age ofstarting immunization, number of children more than 4, and lowparental attitude about immunization (P=0.001) were related tomissed opportunities for immunization.Conclusions There is no difference between proportion of missedopportunities at primary health centers in urban and suburbanarea. Related factors to missed opportunities for immunizationare age of starting immunization older than 3 months, number ofchildren more than 4, and low parental attitude aboutimmunization.